Subclinical Hypothyroidism and Gestational Hypertensive Disorders in a Cohort of Romanian Pregnant Women with Gestational Diabetes Mellitus: A Pilot Study - Muntean Mihai; Săsăran Vladut; Pop Gheorghe Lucian; Muntean Elena Irina; Nyulas Victoria; Mărginean Claudiu (Biomedicines)
Objective: This study aimed to explore whether subclinical hypothyroidism (SCH) treated with levothyroxine in pregnancy complicated by gestational diabetes mellitus (GDM) is associated with an increased risk of gestational hypertensive disorders (GHDs) (gestational hypertension and preeclampsia). Methods: 96 pregnant women with GDM were enrolled in this study and grouped as per the European Thyroid Association criteria into the SCH (n = 21) and euthyroid groups (n = 75). All subjects were tested for anthropometric parameters, maternal glucose homeostasis parameters, lipid levels, thyroid function tests, and blood pressure. All GDM pregnant women received nutritional and insulin therapy where needed, and the SCH group received levothyroxine treatment. Then, the maternal and newborn outcomes were compared. Data were analyzed using Student’s t-test, Mann–Whitney U, and Chi-square tests wherever applicable. p values of <0.05 were considered significant. Results: Patients with GDM and SCH had a pre-pregnancy BMI and BMI at inclusion in the study smaller than those of the euthyroid group (p = 0.0004, p = 0.0009). There were no significant differences between groups regarding the incidence of GHD, preterm prelabor rupture of membranes (PPROMs), macrosomia, low birth weight, and fetal distress (p > 0.05). Patients with GDM and SCH treated with levothyroxine had more premature delivery than the euthyroid group (p = 0.03). Conclusions: Subclinical hypothyroidism treated with levothyroxine in women with GDM does not increase the risk of gestational hypertensive disorders, but is associated with increased risk for prematurity.